Comparative Studied of Degradation of Textile Brilliant Reactive Red Dye Using H2O2, TiO2, UV and Sunlight - mohammed, Forqan; Mousa, Khalid M. (Al-Nahrain Journal for Engineering Sciences, 2019)
In this study sunlight and UV radiation were used to compare the efficiency of decolorization of textile wastewater containing brilliant reactive red dye K-2BP (?max = 534 nm) by the advanced oxidation process (AOP) using (H2O2/sunlight, H2O2/UV, H2O2/TiO2/sunlight, and H2O2/TiO2/UV). The results studied the effect of solution pH, applied H2O2 concentration, TiO2 concentration (nanoparticle), and initial dye concentration were studied. The experimental results showed that decolorization percentage with H2O2/sunlight and TiO2/H2O2/sunlight under the following conditions: - reaction time 150 of minutes, [ 500 ppm] H2O2, [100 ppm] TiO2, pH=3, initial dye concentration =15 ppm and at ambient temperature were 95.7% and 98.42% respectively. For the same conditions using H2O2/UV, H2O2/TiO2 /UV, the percentage of decolorization were 97.85% and 96.33% respectively. The results also indicated that the sunlight is more economic and cost-effective than UV radiation.